High School to College Transition Experiences of Students Admitted in a Chilean Traditional University (CRUCH) through Inclusive Special Admission - Gallardo, Gonzalo; Lorca, Amaya; Morrás, Daniela; Vergara Wilson, Martín (My University, 2014)
Based on a qualitative research design, this study aimed to reconstruct the transition experience from high school to university of a group of young university students from their own perspective. They were accepted through Talent+Inclusion, a special admission program at the Pontificia Universidad Católica de Chile, a traditional institution belonging to the Council of Rectors of Chilean Universities (CRUCH). The perspective of young students, who are key players in the whole learning process, may provide relevant information to the continuous improvement of support programs offered to freshmen when entering higher education. The main findings were summarized, describing the interviewees’ entry trajectory and its principal characteristics, challenges, and difficulties faced by students in their first year, as well as the enablers and projections about future. Differences among academic cultures, identified in students’ narratives, were observed and described, and their impact on inclusion, promotion of learning, and students’ sense of belonging to the university were discussed.
Keywords: transition to college; inclusion and higher education; identity; diversity; affirmative action